The Prakash Padukone story - Sukumar, Dev S. (New Delhi : Niyogi Books, 2013)
Prakash Padukone, born 1955, badminton player from Karnataka, India
Keywords: Padukone, Prakash, -- 1955-; Badminton players -- India -- Karnataka -- Biography; Padukone, Prakash, -- 1955-; Badminton players -- India -- Karnataka -- Biography; Joueurs de badminton -- Inde -- Karnātaka -- Biographies